2012
DOI: 10.1037/a0026488
|View full text |Cite
|
Sign up to set email alerts
|

The impact of social support on the relationship between trauma history and posttraumatic stress disorder symptoms in motor vehicle accident victims.

Abstract: The present study examined how different types of social support differentially moderated the relationship between trauma history characteristics and the development of posttraumatic stress disorder symptoms (PTSS) following a motor vehicle accident (MVA). Two hundred thirty-five MVA victims self-reported levels of social support and trauma history, and were evaluated for PTSS 6- and 12-months post-MVA. Results indicated that after controlling for gender, injury severity and income, number of prior trauma type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
1
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 22 publications
2
35
1
6
Order By: Relevance
“…Social support is a process of providing or exchanging resources with other people (Gabert-Quillen et al, 2011). It has been found that gratitude leads to a higher level of perceived social support (Wood, Maltby, Gillett, Linley, & Joseph, 2008), and the positive relationship between gratitude and social support has been observed in the feelings of being cared for, loved, and highly esteemed (McCullough & Tsang, 2004).…”
Section: Gratitude Social Support and Well-beingmentioning
confidence: 97%
“…Social support is a process of providing or exchanging resources with other people (Gabert-Quillen et al, 2011). It has been found that gratitude leads to a higher level of perceived social support (Wood, Maltby, Gillett, Linley, & Joseph, 2008), and the positive relationship between gratitude and social support has been observed in the feelings of being cared for, loved, and highly esteemed (McCullough & Tsang, 2004).…”
Section: Gratitude Social Support and Well-beingmentioning
confidence: 97%
“…In their literature review, Koch et al ( 2005 ) had found that high negative emotionality contributed substantially to the prediction of PTSD. [Note that Gabert-Quillen et al ( 2012 ) found that number of prior trauma types and subjective response to prior traumas are risk factors for developing PTSD symptoms in MVAs, as is lack of social support.] Normally, PTSD exhibits "signifi cant spontaneous remission" even without treatment, but this is not clearly the case for PTSD litigants.…”
Section: General Introductionmentioning
confidence: 99%
“…It is unknown what is the role that family relationships can play to help the patient recover after injuries. It is possible that injured patients can bene t from family support in seeking and complying with rehabilitation programs, which can facilitate an improved outcome (Gabert-Quillen et al 2012;Nijs et al 2011).On the other hand, injured patients may increase their reliance on family without a focus on improving their own health. Consequently, this may lead to increased disabilities.…”
Section: Introductionmentioning
confidence: 99%